THE MILLENIUM DEVELOPMENT AGENDA AND DEMOCRACY IN NIGERIA, 1999-2004 - Eze, M.C (University of Nigeria Journal of Political Economy, 2022)
This article overviews the relationship that exists between the contemporary orthodoxy-the millennium development agenda and democracy, using Nigeria as a case evaluation. According to the orthodoxy, development in the ‘South’ depends on the reappraisal of the respective roles of the state and market, institutional and economic reforms, and good governance, which finds expression in democracy. This article argues that the principles of these reforms tend towards dictatorship, orchestrate increased poverty and deepen underdevelopment. Thus, the orthodoxy is an instrument of “Northern’ exploitation and subordination of the South, and does not reinforce democracy. A mass oriented model of development that reinforces democracy is therefore recommended.